Analisis Faktor Risiko Kejadian Kurang Gizi Pada Balita Di Puskesmas Pembantu Tanjung Sari - Yuniati Laia; Zuraidah Nasution; Asriwati Asriwati (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Abstract-Cases of malnutrition in the Tanjung Sari sub publict health center there were 7 (1.26%) cases when viewed from the birth rate in the work area, while for the case of malnutrition in the city of Medan, Tanjung Sari sub public health center contributed 0.9% malnutrition (5 children under five). This study aims to determine the risk factors for the incidence of malnutrition in children under five at the Tanjung Sari Sub Public Health Center. This research was an analytic survey with a cross sectional study design conducted at the Tanjung Sari sub-health center from July to August 2022 with a total sample of 81 people. Data were analyzed using Chi Square test and Logistic Regression. Based on the results of the study, it was found that mother's knowledge (p = 0.001), family income (p = 0.025), exclusive breastfeeding (p = 0.011), history of infectious diseases (p = 0.000), number of family members (p = 0.001), access to services Health (p=0.000) was associated with the incidence of malnutrition in children under five at the Tanjung Sari sub public health center. The results of multivariate analysis with logistic regression concluded that family income was the dominant factor influencing the incidence of malnutrition in children under five. It is recommended that the results of this study become input for the puskesmas in increasing public knowledge about the fulfillment of toddler nutrition. Such as the selection of foods that contain high nutrition at low prices. Keywords: Income, Infection, Malnutrition, Toddler